2013
DOI: 10.1080/01457632.2013.812493
|View full text |Cite
|
Sign up to set email alerts
|

Condensation in a Square Minichannel: Application of the VOF Method

Abstract: A number of steady-state numerical simulations of condensation of R134a at mass fluxes of 400 kg m−2 s−1 and 800 kg m−2 s−1 inside a 1-mm square cross section minichannel are proposed here and compared against simulations in a circular cross section channel with the same hydraulic diameter. The volume of fluid (VOF) method is used to track the vapor–liquid interface, and the effects of interfacial shear stress, surface tension, and gravity are taken into account. A uniform wall temperature is fixed as a bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…The same approach was also adopted in Bortolin et al [27], Kharangate et al [29], and Lee et al [16]. The basic equations for the continuity, momentum, energy, turbulence kinetic energy, and the specific dissipation rate are the same with those of single-phase flow as listed in Eq.…”
Section: Governing Equationsmentioning
confidence: 93%
See 2 more Smart Citations
“…The same approach was also adopted in Bortolin et al [27], Kharangate et al [29], and Lee et al [16]. The basic equations for the continuity, momentum, energy, turbulence kinetic energy, and the specific dissipation rate are the same with those of single-phase flow as listed in Eq.…”
Section: Governing Equationsmentioning
confidence: 93%
“…3 and Eq.4 are based on the Lee [31] model which is widely adopted for condensation [16,17,[25][26][27][28][29] and evaporation [32,33] simulations.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the steam flow condensation in tube, as well as the two-phase flow regime map, many investigations have been carried out, scholars have proposed many theoretical models about the steam flow condensation in tube, including VOF [20], Level set [21] and the interface tracking method [22][23][24][25][26][27][28]. Both VOF and the Level set model are based on the number of grids, so as a result, one can hardly obtain an accurate result when the film is thin enough.…”
Section: Condensate Film Development Inside Finned Flat Tubementioning
confidence: 99%
“…Bortolin et al [6] presented a number of steady-state simulations of condensation of R134a at mass fluxes G = 400 kg m -2 s -1 and G = 800 kg m -2 s -1 inside a 1 mm square cross section minichannel. The gravity force has a minor effect on the liquid-vapour interface distribution in the square minichannel; the authors found that at these mass velocities, the heat transfer mechanism is dominated by shear stress and surface tension.…”
Section: Introductionmentioning
confidence: 99%